The release of contaminants from steel slags and natural aggregates: Evaluation of toxicity and genotoxicity. (25th September 2020) - Alias, Carlotta; Feretti, Donatella; Benassi, Laura; Abbà, Alessandro; Gelatti, Umberto; Sorlini, Sabrina; Zerbini, Ilaria; Piovani, Giovanna
Abstract: Steel slags (SS) are the major waste produced by iron and steel industry. Slags may be reused as recycled materials, instead of natural aggregates (NA), to reduce the final disposal in a landfill and the exploitation of raw materials. However, the reuse of SS may generate a potential release of toxic compounds for the environment and humans. The purpose of this study was to evaluate the toxicity and genotoxicity of SS, in comparison with NA, by using an integrated chemical‐biological approach to enable their safe reuse in engineering applications. Leaching solutions from samples were obtained by using short‐term leaching tests (CEN EN 12457‐2, 2004) usually adopted for the evaluation of waste recovery and final disposal. Chemical analyses of leachates were performed according to the Italian legislation on waste recovery (Ministerial Decree 186/2006). The leaching solutions were assayed by using toxicity test on Daphnia magna. Moreover, mutagenicity/genotoxicity tests on Salmonella typhimurium, Allium cepa, and human leucocytes and fibroblasts were carried out. The releases of pollutants from all samples were within the limits of the Italian legislation for waste recovery. Despite the effects that SS and NA could have on different cells, in terms of toxicity and genotoxicity, globally, SS do not seem to be any more hazardous than NA. This ecotoxicological assessment, never studied before, is important for promoting further studies that may support the decision‐making process regarding the use of such types of materials.